Neutrophil-To-Lymphocyte Ratio As A Diagnostic Predictor And Initial Management In Sepsis-Induced Acute Kidney Injury: A Systematic Review Based On Recent Studies - Ni Made Dwitya Arianingtyas; Putu Feby Miswari Dewi; Putu Yogi Pranata (International Journal Labs, 2026)
Sepsis is a leading cause of Sepsis-Induced Acute Kidney Injury (SI-AKI) and contributes substantially to high morbidity and mortality among critically ill patients. The neutrophil-to-lymphocyte ratio (NLR) is a systemic inflammatory biomarker that is readily obtained from routine blood tests and has potential value as a diagnostic predictor and a basis for early management of SI-AKI. This systematic review aims to evaluate the role of NLR as a diagnostic predictor and a basis for early management in patients with SI-AKI based on recent studies. This study is a systematic review conducted in accordance with the PRISMA 2020 guidelines. A literature search was performed using PubMed and Google Scholar databases for articles published between 2021 and 2025. Included studies were original articles involving adult populations, assessing NLR as a parameter, and reporting outcomes related to SI-AKI. The methodological quality of included studies was assessed using the Joanna Briggs Institute (JBI) Critical Appraisal Tool. A total of five observational studies met the inclusion criteria. Most studies demonstrated significantly higher NLR values in septic patients who developed SI-AKI compared with those who did not. Several studies also reported an independent association between elevated NLR and AKI progression as well as increased mortality. However, one study found no significant association between NLR and certain clinical outcomes, including the need for mechanical interventions and length of hospital stay. NLR has the potential to be used as an early diagnostic parameter and a risk stratification tool in SI-AKI